Predictors of quality of life for autistic adults. Issue 8 (7th May 2018) - Mason, David; McConachie, Helen; Garland, Deborah; Petrou, Alex; Rodgers, Jacqui; Parr, Jeremy R.
Abstract: Research with adults on the autism spectrum is as yet limited in scope and quality. The present study describes quality of life (QoL) of a large sample of autistic adults in the UK and investigates characteristics that may be predictive of QoL. A total of 370 autistic adults from the Adult Autism Spectrum Cohort‐UK (ASC‐UK) completed the WHOQoL‐BREF, and the Social Responsiveness Scale (SRS, autism symptom severity), along with the ASC‐UK registration questionnaire giving information on mental health and their life situation. QoL for autistic adults was lower than for the general population for each WHOQoL domain. Younger participants reported higher QoL than older participants in psychological and environment domains. Males reported higher physical QoL than females, and females reported higher social QoL than males. Significant positive predictors of QoL were: being employed (physical QoL), receiving support (social and environment QoL), and being in a relationship (social QoL). Having a mental health condition and higher SRS total score were negative predictors of QoL across all four domains. Autistic adults require access to effective mental health interventions, and informal and formal support for their social difficulties, to improve their quality of life. Autism Res 2018, 11: 1138–1147 . © 2018 The Authors Autism Research published by International Society for Autism Research and Wiley Periodicals, Inc. Lay summary: There has been limited research into the lived experience of autistic adults. Using the World Health Organization quality of life measure, we found that autistic people (370) in the UK reported their quality of life to be lower than that of the general population. Better quality of life was associated with being in a relationship; those with a mental health condition had poorer quality of life. This research suggests some ways in which autistic people can be helped to improve their quality of life.